Analysis of Speech and Language Development in Early Childhood Students:Observational Assessment - Azka Aqillah Nasywa; Lilis Patmiah (Ananda: Jurnal Pendidikan Anak dan Remaja, 2025)
This study aims to analyze the development of speech and language skills in early childhood based on the results of observations on a 4-year-old 11-month-old child named AZA. Observations were carried out for four weeks using instruments that refer to the indicators from Permendikbud No. 137 of 2014 paragraph 1, covering three main aspects: receptive language (the ability to understand language), expressive language (the ability to express language), and early literacy. The results showed that children's language skills developed gradually from the stage of Not Developing, Starting to Develop, to Developing As Expected in most indicators. Children show the ability to understand two instructions at the same time, listen to stories, express opinions, and recognize and write their own names. These findings show the importance of continuous stimulation from the home environment to support children's language development. This study confirms that the process of language development in early childhood requires a consistent, fun, and interactive approach to achieve optimal outcomes.